Pengaruh Profesionalitas dan Disiplin Kerja Terhadap Kualitas Pelayanan Administrasi Kependudukan Di Kelurahan Duren Seribu Kecamatan Bojongsari Kota Depok - Ahmad Sabani; A.H. Rahadian (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
The objective of this research is to analyze the Effect of Professionalism and Work Discipline on the Quality of Population Administration Services at the Office of Duren Seribu Urban Village, Bojongsari District, Depok City, parlially and simultaneously. The selected theories include Professionalism Theory by Pettern Jr., (in Sedarmayanti, 2012'.76-77), Work Discipline Theory by Rivai and Sagala (2011:825) and Service Quallty Theory by Lovelock (in Latunreng, 2010:160). This research uses quantitative Explanatory Method with quantitative descriptive approach. The population of this research is 1.576 recipients of population administration services for the January- December 2019 period and the sampling technique used is Slovin (5%) so that there are 319 samples obtained. The results of this research show that (1) The effect of Professionalism on the Quality of Population Administration Services at the ffice of Duren Seribu Urban Village, Bojongsari District, Depok City is at 55.1% and there is a positive and significant effect; (2) The effect of Work Discipline on the Quality of Population Administration Services at the Office of Duren Seribu Urban Village, Bojongsari District, Depok City is at 54.4% and there is a positive and significant effect; and (3) The effect of Professionalism and Work Discipline simultaneously on the Quality of Population Administration Services at the Office of Duren Seribu Urban Village, Bojongsari District, Depok City is at 59.2% and there is a positive and significant effect.